Morphological and immunohistochemical comparison of the pituitary gland between a tropical paracheirodon axelrodi and a subtropical aphyocharax anisitsi characids (Characiformes: Characidae) - Rincón Camacho, Laura (2020)
Cardinal tetra Paracheirodon axelrodi and bloodfin tetra Aphyocharax anisitsi are two species of characids with high trade value as ornamental fish in South America. Although both species inhabit middle water layers, cardinal neon exhibits a tropical distribution and bloodfin tetra a subtropical one. Generally, these species are difficult to grow, so it becomes essential to know some key components of the neuroendocrine system to achieve their reproduction in captivity. Considering the importance of deepening the knowledge of the reproductive physiology through functional morphology, for the first time in this work we performed an anatomical, morphological and immunohistochemical analysis of the pituitary gland of these two species. In both species, a leptobasic type pituitary is found in the ventral zone of the hypothalamus and it is characterized by a neurohypophysis which has a well-developed pituitary stalk and a globular adenohypophysis. The pituitary components, characterized by histochemistry and immunohistochemistry, shows a distribution pattern of cells types similar to other teleost species, with only slight differences in the distribution of βFSH and βLH for P. axelrodi.